(3bHS GdGbJOGA Edi hab GdSYGOI hfLM GdGgJOGAs - (3SdjeGf Hf YHO Gddg Hf YHO GdQMef GdYHGSjs ((3eMeO Hf eMeO GdHdjGfi s)
(3ChdgG (B:s
(3Efg JbGSeJ eWGdH GdQGZHjf Edi bSejf OfjGhi hGNQGhi s
(3BNQgG (B:s
(3UbI GdHSW hGdJcSjQ HSWg GSeg GdMajX hGSe GddWja abS Ydjg eG TFJ s
(3Vef eLehY , JQJjHgG (B: (3GdJGSYs
(3HgG fXGe GdJYbjHIs
(3eUOQ GbJfGA GdCUd (B:s
(3GeHQhRjGfG (B(B 58) s
Keywords: (3GdMQha h GdChaGbs